Belt & Road Initiative in Times of 'Synchronized Downturn' Issues, Challenges, Opportunities - Visvizi, Anna; Lytras, Miltiadis (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Nearly ten years since the official launch of the Belt and Road Initiative (BRI), an understanding of what the initiative's objectives are consolidated. However, the short-, mid-, and long-term implications of the initiative are less clear. This is reflected in academic research, as well as in policy-oriented publications stemming from the global think-tank sector. This collection adds to this debate by offering a glimpse into selected aspects of BRI and its development, including the applicability of existing theories of trade to the case of BRI, the specificity of investment modes associated with BRI, sustainability, SDGs, socio-cultural issues, and many other implications. Due to its focus on diverse aspects of BRI, this collection will be of interest to students of international economics, international relations, and related subjects.